2006
DOI: 10.1387/ijdb.062177sy
|View full text |Cite
|
Sign up to set email alerts
|

Xtbx6r, a novel T-box gene expressed in the paraxial mesoderm, has anterior neural-inducing activity

Abstract: T-box proteins are important transcriptional regulators in animal development. We searched the Xenopus laevis expressed sequence tag (EST) database using zebrafish tbx24 (Ztbx24) as a query and found a sequence. We then obtained corresponding clones from a neurula cDNA library. This novel gene has a T-box showing 53% homology with Xenopus laevis tbx6 (Xtbx6) and 51% with Ztbx24 at the amino acid level and is relatively close to Xtbx6 indicated by alignment analysis. In situ hybridization showed that it is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…3 This VegT/Nodal cascade leads to the zygotic expression of a number of genes, among which are those that encode the T-box transcription factors Eomesodermin, 58 Brachyury (there are in fact three distinct brachyury genes in Xenopus), 59-61 the zygotic splice variant of VegT, known as Antipodean, 62,63 and the T-box transcription factors Tbx6 and Tbx6-related. [64][65][66][67] Recent studies indicate that downregulation of zygotic VegT/Antipodean is We have indicated where a number of the genes that are the primary focus of this review are thought to act. That said, and as noted in the text, it is often the case that genes expression is co-dependent, so that simple linear pathways should be considered skeptically.…”
Section: Neural Crest Induction and Migration In Xenopusmentioning
confidence: 99%
“…3 This VegT/Nodal cascade leads to the zygotic expression of a number of genes, among which are those that encode the T-box transcription factors Eomesodermin, 58 Brachyury (there are in fact three distinct brachyury genes in Xenopus), 59-61 the zygotic splice variant of VegT, known as Antipodean, 62,63 and the T-box transcription factors Tbx6 and Tbx6-related. [64][65][66][67] Recent studies indicate that downregulation of zygotic VegT/Antipodean is We have indicated where a number of the genes that are the primary focus of this review are thought to act. That said, and as noted in the text, it is often the case that genes expression is co-dependent, so that simple linear pathways should be considered skeptically.…”
Section: Neural Crest Induction and Migration In Xenopusmentioning
confidence: 99%
“…Weak pMesogenin2 expression was detected in the head region by whole-mount in situ hybridization. RT-PCR from cDNAs obtained by dissection of stage 33 embryos into four fragments (head-1, head-2, trunk, and tail; Yabe et al, 2006) revealed that pMesogenin2 was expressed only in the tail region (data not shown) suggesting that the weak signal observed in the head region was non-specific.…”
Section: Pmesogenin2/mespo2 Is a Novel Bhlh Genementioning
confidence: 99%
“…The Hind III-Sma I (526 bp, pMesogenin1) or EcoR I-Xho I (504 bp, Xtbx6) fragment from these plasmids was labeled with 32 P, and subsequent screenings were carried out as described by Yabe et al (2006). GenBank Accession Numbers for Xtbx6 and pMesogenin2genomic D NA sequences are AB462326 and AB462327, respectively.…”
Section: Genomic Library Screeningmentioning
confidence: 99%
See 2 more Smart Citations